2023
DOI: 10.1111/dar.13635
|View full text |Cite
|
Sign up to set email alerts
|

Do Australian adolescents with permission to drink at home engage in different alcohol use behaviours and experience more harms than those without such permission?

Abstract: Introduction Around half of Australian students aged 16–17 are estimated to have drunk alcohol in the past month, with 11% drinking at ‘risky’ levels. This study investigated: (i) how many Australian adolescents aged 16–17 had parental permission to drink at home in 2016/17 and whether prevalence differed by adolescent sex; (ii) whether adolescents allowed to drink at home had drunk more recently and were drinking greater quantities; (iii) if adolescents allowed to drink at home experienced more alcohol‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Finally, while home drinking is much more common in older people, this consumption may be influencing younger people in the home. Quinn et al [12] found that young people with permission to drink at home experienced more alcohol-related harms than those who did not have said permission. The authors contextualise this finding by referring to previous research indicating a belief among parents that supervised consumption at home could reduce future harms from alcohol for their children.…”
mentioning
confidence: 99%
“…Finally, while home drinking is much more common in older people, this consumption may be influencing younger people in the home. Quinn et al [12] found that young people with permission to drink at home experienced more alcohol-related harms than those who did not have said permission. The authors contextualise this finding by referring to previous research indicating a belief among parents that supervised consumption at home could reduce future harms from alcohol for their children.…”
mentioning
confidence: 99%